Enhancing Digital Identity and Access Control in Event Management Systems Using Sui Blockchain - Suthir Sriram; P. R. Tharaniesh; Priyanka Saraf; Nivethitha Vijayaraj; Thangavel Murugan (IEEE Access)
The evolution of blockchain technology presents transformative potential for event management, particularly in enhancing security, transparency, and efficiency across the industry. This paper introduces a blockchain-based event management system that leverages Sui blockchain technology to address critical challenges such as ticket fraud, data security, and high transaction fees, which are prevalent in traditional event management systems. The proposed system incorporates several innovative features: Tickets to the System: Utilizing the concept of NFT, the system guarantees that each ticket is unique, is tamper proof and cannot be forged. It also ensures the validity of tickets and at the same time ensures that the ticket is transferable back and forth while the ownership of the ticket is wholly and clearly disclosed. zkLogin for Seamless User Authentication: zkLogin is then implemented in the platform to ensure users can be authenticated in a Privacy-Preserving manner while at the same time having High Security. This mechanism can be highly beneficial for the users because they can log in as quickly and discreetly as possible without any threat to their accounts’ safety. Suiet & Sui Wallet for Cost-Effective Transactions: Merging of Suiet and Sui Wallet enables cheap transactions and something that is always financially draining when using blockchain systems is deposits costly transactions fees. This makes the platform to be open to a wider market especially to those who are organizing small scale events. Due to decentralizing the event management process the platform reduces all possible risks that can occur in condition of centralized systems like for example single points of failure and also creates higher transparency of ticket sales and distribution. Furthermore, this greatly decentralizes the system which drastically decreases the transaction costs making the solution fiscally sustainable for events of various scales. This paper also presents the design and implementation of the platform as well as the flexibility of the platform depending on the kind and size of the event. The research indicates that the use of this blockchain technology increases the security and the verifiability of the event tickets in addition to providing a solution to the whole flow of the event beginning from ticket distribution to ticket authentication and transaction management.